Critical single-domain grain sizes in elongated iron particles: implications for meteoritic and lunar magnetism - Muxworthy,AR; Williams,W (Geophysical Journal International, 2015)
Kamacite particles (Fe–Ni, Ni < 5 per cent), are very common in extra-terrestrial materials, such as meteorites. It is normally assumed that for kamacite particles to be reliable recorders of magnetic fields, they need to be magnetically uniform (single domain, SD) and thermally stable. Larger particles subdivide into non-uniform multidomain (MD) magnetic structures that produce weaker magnetic signals, while small SD particles become magnetically unstable due to thermal fluctuations and exhibit superparamagnetic behaviour. In this paper we determine the first micromagnetic calculation of the stable SD range domain-state phase diagram for metallic iron; previous calculations were analytical. There is a significant increase in the critical size for the SD/MD threshold size, for example, for cube-shaped iron particles, the critical SD/MD threshold has now been estimated to be 25 nm, compared to 17 nm for previous estimates. The larger critical SD/MD threshold size for iron, agrees better with previously published nanometric observations of domain state for FeNi particles, then early analytical models.